THE EFFECT OF THE VICTIM’S CONSENT RESULTING FROM DANGEROUS SPORTS ON THE RIGHT OF COMPENSATION - Dr. Osama Nahar Ismail Almajali, Mohammed Khalif Mujali Almajali (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The responsibility of the perpetrator of a harmful act in Jordanian civil law is based on the availability of three pillars, which are: the act of harm, the harm, and the causal relationship between the act and the harm; So that if the harmful act results in harm to another person, the injured person can claim compensation for the damage , and in this case the harm done to the injured is without the consent of the injured, but if the injured is satisfied with the harmful act that causes him the harm, then can he claim compensation for the damage that was caused with it? , And the consent of contributory damage do you arrange legal effect varies depending on the type of damage the case or potential? Would this consent issued by the injured be a wrong behavior affecting his right to compensation? Can the defendant invoke this consent to deny civil liability for it? , The consent of the injured is either a legal act is subject to civil law sometimes, Or is subject to criminal law at other times and called the victim, and one of the main problems raised by the consent of the injured for damage in determining the legal nature to which it belongs , and the consent of the injured for the damage to be in one of two forms: one satisfaction injury case, and which satisfies the injured of the damage wrought by himself deliberately . And the second is satisfaction with the potential harm, in which the injured knows clearly about the possibility of the harm occurring, and he is able to estimate the nature of the harm that could happen, and yet he accepts it and bears its consequences and risk.